Stalin’s Terror
XVIII, 255 p.
Keywords: The British, Irish, Russian, American, German and Austrian contributors examine the intricate nature of the mass repression unleashed by the Stalinist leader of the USSR during 1937-38. The first part of the collection deals with annihilation policies against the Soviet elite and the Communist International. The second section of the volume looks at mass operations of the secret police (NKVD) against social outcasts, Poles and other 'hostile' ethnic groups. The final section comprises micro-studies about targeted victim groups among the general population.